THE MODERATION ROLE OF INSTITUTIONAL OWNERSHIP ON THE QUALITY OF CARBON EMISSION DISCLOSURE, ENVIRONMENTAL PERFORMANCE AND CORPORATE FINANCIAL PERFORMANCE - Indira Shinta Dewi shinta; Dede Nurdiniah (Jurnal Satya Mandiri Manajemen dan Bisnis, 2026)
ABSTRACT This study aims to examine the impact of the quality of carbon emissions disclosure and environmental performance on financial performance, with institutional ownership as a moderating variable. This study employs a quantitative approach and panel data regression. It analyses companies listed in Indonesia between 2020 and 2025 that publish sustainability reports and comply with the PROPER system. The results indicate that the quality of carbon emissions disclosure has a significant negative impact on financial performance. Environmental performance does not have a significant direct impact. Institutional ownership significantly strengthens the relationship between the quality of carbon emissions disclosure and financial performance. Conversely, institutional ownership weakens the relationship between environmental performance and financial performance. These findings suggest that institutional ownership acts as a heterogeneous moderator. The uniqueness of this study lies in the development of carbon emissions disclosure quality as a multidimensional construct encompassing completeness, accuracy, independent verification, and strategic integration. This study also positions institutional ownership as a complementary resource whose moderating effect is not always positive. Unlike previous studies that assumed consistent moderation, this study demonstrates that institutional ownership can either strengthen or hinder the economic conversion of various environmental capabilities. The implications of this study suggest that companies need not only to improve carbon disclosure and environmental activities but also to consider the characteristics of institutional investors, who may be short-term oriented, thereby conflicting with long-term environmental investments. Keywords: Quality of carbon emissions disclosure, Environmental performance, Financial performance, Institutional ownership